INVENTORY OF MEDICINAL FLORA FROM THAL DESERT, PUNJAB, PAKISTAN - Shaheen, Humaira; Qureshi, Rahmatullah; Akram, Abida; Gulfraz, Muhammad (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: This article reports the preliminary findings of an ethno-botanical survey that was carried out in the Thal Desert, Punjab, Pakistan during 2010 to 2013. The aim of this study was to document the traditional use of medicinal plants from the study area.Materials and Methods: The whole area was surveyed for inventorying medicinal flora by using a semi-structured questionnaire. Results: The people of the study area are extremely knowledgeable, hence reported 120 plants which are being used in treating various human diseases. The detailed inventory including botanical name, parts used, method of preparation and diseases treated is provided in this paper.Conclusion: This study revealed that the inhabitants possessed empirical knowledge of medicinal plants which would be useful in developing health care products and preserving traditional cultures as well as phyto-diversity.